Torbangun Leaf Extract (Coleus Amboinicus) Effect on Breast Milk Production, Perineal Wound Healing and Increasing HB Levels in Postpartum Mothers - Eti Kuswandari; Novi Budi Ningrum (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Physiological needs including maternal nutritional intake increase due to the need to produce breast milk, the healing process of perineal wounds and decreased hemoglobin levels. One effort that can be done to increase the rate of breast milk production/secretion, accelerate wound healing and increase hemoglobin levels is through the use of traditional herbal medicines. There are several plants that are believed by generations and have also been scientifically proven to support in increasing the quality and quantity of breast milk, accelerating wound healing and increasing hemoglobin levels of postpartum mothers. For example, the Torbangun leaves (Coleus amboinicius). This study examines the effect of administering Torbangun leaf extract (Coleus amboinicus) on breast milk production, perineal wound healing and increasing of HB levels in postpartum mothers. This type of research method uses a quantitative research design with a quasi-experimental approach with a pretest-posttest control group design to determine the effect of administering Torbangun leaf extract (Coleus amboinicus) on breast milk production, perineal wound healing, and increasing of hemoglobin levels in postpartum mothers. This research was conducted at Permata Hati Hospital Malang within a 14-day treatment period. The sampling technique in this study used purposive sampling, namely the selection of 32 postpartum mothers who were divided into two groups, namely the intervention group and the control group and which were analyzed using the Wilcoxon test. The results of this study obtained a Z-count value of -3.220 with a significance value of 0.001 (p0.05) on the breastfeeding variable, on the perineal wound healing variable the Z-count value was -3.951 with a significance value of 0.001 (p0.05) and on the HB (Hemoglobin) level variable the Z-count value was -1.433 with a significance value of 0.0152 (p0.05). From the results of this study, it can be concluded that there is a significant effect of administering Torbangun leaf extract on breast milk production, the healing of perineal wounds and the increasing of HB levels in postpartum mothers.